Penerapan Kombinasi Metode AHP MOORA Pada Sistem Pemilihan Wedding Organizer (WO) di Daerah Bogor - Arif Maulana; Bobi Agustian (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Wedding Organizer is one of the media that can help the bride and groom in solving problems related to the wedding, and can provide solutions or suggestions about the problems being faced by the bride and groom it can give satisfaction to the bride and groom who will hold a wedding, because it can provide rational consideration. Many people in the Bogor area have difficulty in making choices in using the services of a wedding organizer in accordance with the desired needs, with considerations such as the budget of the bride and groom, the concept of the wedding and so forth. From the problems that occur required a system that can provide decisions and is able to assist the public in determining the selection of wedding organizer services as needed. In this study applied a combination of two methods of SPK is AHP (Analityc Hierarchy Process) and MOORA (Multi-Objective Optimization on the Basis of Ratio Analysis). Based on the test results obtained by the percentage of UAT 73%, so the system is feasible to use. The system successfully implemented SPK by combining AHP and MOORA methods, and obtained a consistency index value of 0.1 and a consistency ratio of 0.08 so that it can be concluded that the criteria used are consistent.